Studies on the Action Mechanism of the Antihemostatic Effect of lodopeptides - Golub, A.L; Mende, T.J (Thrombosis and Haemostasis, 1976)
A synthetic iodopeptide having a glutamic acid-diiodotyrosine molar ratio of 1:1 has been shown to be an effective anticoagulant both in vivo and in vitro. Contrasted with heparin the following general conclusions may be made regarding its action. The iodopeptide does not act through the inactivation of thrombin in plasma. Iodopeptide does interact with fibrinogen to form a complex which, in vitro, is not soluble in buffered saline at physiological pH. At pH 8, iodopeptide interacts with fibrinogen to form a soluble complex in the presence of 0.9 % NaCl that is not coaguable either by thrombin or Crotalus venom enzymes. All the available evidence indicates that the fibrinogen to fibrin conversion is not inhibited under these conditions, but that fibrin, once formed, is not able to polymerize due to interference by iodopeptide. Similar results were obtained with heparin in vitro with thrombin-fibrinogen mixtures in the absence of NaCl.Studies with Russell’s viper venom in native PRP strongly suggest that the iodopeptide also interferes with processes in the early coagulation pathway associated with prothrombin activation.